Kansans move into health: a program evaluation - Schrage, Andrea Michelle (Kansas State University, 2010)
Heart disease, cancer, stroke, and diabetes are the leading causes of death in the United States. In addition, the prevalence of obesity has significantly increased since the 1970s. In Kansas, 37% of adults are overweight and 24% are obese. These chronic diseases and conditions tend to be prevented by and/or managed with both adequate physical activity and a healthy diet rich in fruits, vegetables, and whole grains. In Kansas 48.5% of adults meet the current recommendations for physical activity set by the American Heart Association, while 20% of adults consume the recommended amounts of fruits and vegetables. Public health officials need to work together to encourage Kansas adults to increase their participation in physical activity and consumption of fruits and vegetables to help prevent future health problems or manage current chronic diseases. To help address these health issues in Kansas, Kansas State University Research and Extension developed the 8-week Kansans Move into Health nutrition and physical activity program, building its framework around the Theory of Planned Behavior (TPB). Using TPB, participants address attitudes and perceived norms as well as perform specific behaviors associated with healthy eating and physical activity. The purpose of this study was to evaluate the effectiveness of condensing the 8-week nutrition and physical activity program into four one-hour classes using a pre- and post-survey. Nineteen participants from the Johnson County community signed up to participate with 63% (n=12) completing the program. Results indicated that participants changed their belief that nutritious foods are more expensive (p≤0.05). Furthermore, participants gained knowledge in how to prepare healthy snacks that are quick and easy. All other measures did not change (n=19; p>0.05). Future research evaluating longer program interventions could better assess attitudes and perceived norms associated with healthy behaviors and determine whether the increase in knowledge leads to behavior change.
Keywords: Nutrition; Exercise; Intervention; Theory of Planned Behavior; Public Health; Health Sciences, Nutrition (0570); Health Sciences, Public Health (0573)